A METHODOLOGY FOR ASSESSMENT THE EFFICIENCY OF WAGE SYSTEM IN PUBLIC (MUNICIPAL) ESTABLISHMENTS: THE FIRST TESTING RESULTS IN THE SOCIAL SPHERE - N. Volgin; I. Demidov (Управленческие науки, 2015)
The article deals with the main tasks, stages and investigation results made by the scientific staff of All-Russia centre of living standard on the demand of the Research Institute of Russia Ministry of Finance in the field of working - out and testing the methodology for assessment the efficiency of wage system in the public sector. The article analyses in-system the concepts of wages return and wages liquidity, the worked-out methodology for assessment the efficiency of wage system (MAEWS) in public and municipal establishments is revealed. It is supported by the evidence the necessity of introduction the compensating performance ratio of payment (PRP) in getting the results concerning the organization, branch, temporary period, etc. The given ratio was achieved by expert way in the result of separate investigation in which the ambitious Russian experts in the field of economics and remuneration of labour had taken part. The methods of calculating the labour results and costs are given. At that the monetary method allows to investigate the ratio of real remuneration of labour (RRL) and labour performance against the general financial indices, and also separately against the budget and off-budget financing at the level of separate employees and top managers. The investigation was done as exemplified by thirty-two budgetary institutions from different regions of the Russian Federation, assigning them to effective, very effective, ineffective, very ineffective is made against the criteria defined through the expert way corrected to the compensating performance ratio of payment (PRP), on the basis of calculating the indicators of wage system efficiency and official statistic data. It is justified that the wage system efficiency is somewhat higher in health care institutions as compared to institutions of culture and education. The article presents the possibility to use the worked-out methods at the individual, regional, national level, its usage not only for the budgetary institutions but also for the institutions of the commercial sector. The characteristic interrelation between the organizations efficiency indices and their administrators is introduced.